Botulinum toxin in the masseter muscle: Lingering effects of denervation. Issue 5 (15th September 2021) - Baldwin, Michael C.; Liu, Zi Jun; Rafferty, Katherine L.; Keith, Andrew; Tamasas, Basma; Kaiyala, Karl; Herring, Susan W.
Abstract: Botulinum neurotoxins (BoNTs) are paralytic agents used to treat a variety of conditions in jaw muscles. Although their effect is considered temporary, there are reports of persistent functional changes. Using rabbits that received BoNT injection in one masseter muscle, the recovery of neuromuscular connection was investigated using nerve stimulation to evoke an electromyographic (EMG) response, and the recovery of muscle fibers was investigated using histological morphometry and bromodeoxyuridine (BrdU) immunohistochemistry. One month after treatment, evoked EMG was greatly reduced in both amplitude and duration, indicating that little reinnervation had taken place. Muscle fibers were atrophied and collagenous tissue was increased. Three months after treatment, evoked EMG duration was normal, indicating that at least some neuromuscular junctions were functional. Histologically, some muscle fibers were hypertrophied, some were still atrophied, and some appeared to have died. Fibrosis was still apparent amid slight increases in dividing cells and regenerating fibers. The histological effects of BoNT were evident although attenuated at a distance of about 1 cm from the injection level, but no regional differences could be discerned for the evoked EMGs. In conclusion, there were persistent muscular deficits seen 3 months after BoNT treatment that may have been caused by the failure of some affected muscle fibers to become reinnervated.